Management of acute and delayed chemotherapy-induced nausea and vomiting: role of netupitant–palonosetron combination - Janicki PK (Dove Medical Press, 2016)
Piotr K JanickiDepartment of Anesthesiology and Perioperative Medicine, Milton S Hershey Medical Center, Pennsylvania State University College of Medicine, Hershey, PA, USAPurpose: The purpose of this review is to summarize and discuss the recently published data (both original studies and reviews) on the oral medication NEPA, consisting of netupitant (a neurokinin-1 receptor antagonist [NK1RA], 300 mg dose) and palonosetron (5-hydroxytryptamine [serotonin or 5HT] type 3 receptor antagonist [5HT3RA], 0.5 mg dose), in the prevention of the acute and delayed nausea and vomiting in patients receiving highly or moderately emetogenic chemotherapy.Methods: This review was based on the very limited number of available published trials consisting of two Phase III studies and one Phase II dose-selecting trial.Results: These studies demonstrated some therapeutic benefits of NEPA over related chemotherapy-induced nausea and vomiting (CINV) prophylaxis management, as well as its beneficial safety profile. In particular, compared with single-dose 0.5 mg palonosetron, the complete response rates for all phases of CINV for the first cycle of highly emetogenic chemotherapy (with cisplatin), as well as anthracycline–cyclophosphamide-based moderately emetogenic chemotherapy, were significantly higher for single-dose NEPA. The high efficacy of NEPA in terms of prevention of CINV continued throughout repeated cycles of highly and moderately emetogenic therapies.Conclusion: It is currently recommended that patients who are administered highly emetogenic chemotherapy regimens should obtain a three-drug combination consisting of NK1RA, 5HT3RA, and dexamethasone. The recently available oral combination of NEPA plus dexamethasone provides an additional pharmacological management option that could be considered in this scenario.Keywords: chemotherapy-induced nausea and vomiting, palonosetron, netupitant, NEPA, safety, pharmacology, outcomes